2014
DOI: 10.1371/journal.pone.0098570
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Tissue Engineering Using Dermis Isolated Adult Stem Cells: The Use of Hypoxia during Expansion versus Chondrogenic Differentiation

Abstract: Dermis isolated adult stem (DIAS) cells, a subpopulation of dermis cells capable of chondrogenic differentiation in the presence of cartilage extracellular matrix, are a promising source of autologous cells for tissue engineering. Hypoxia, through known mechanisms, has profound effects on in vitro chondrogenesis of mesenchymal stem cells and could be used to improve the expansion and differentiation processes for DIAS cells. The objective of this study was to build upon the mechanistic knowledge of hypoxia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Hypoxia likely increased cell proliferation in a cell source-dependent manner. Kalpakci et al found that hypoxic treatment (5% oxygen) resulted in a significant decrease in number of dermis isolated adult stem cells at days 7, 9, and 11 of culture and a lower colony forming unit – fibroblast (CFU-F) compared with normoxic culture [40]. …”
Section: Hypoxic Preconditioningmentioning
confidence: 99%
“…Hypoxia likely increased cell proliferation in a cell source-dependent manner. Kalpakci et al found that hypoxic treatment (5% oxygen) resulted in a significant decrease in number of dermis isolated adult stem cells at days 7, 9, and 11 of culture and a lower colony forming unit – fibroblast (CFU-F) compared with normoxic culture [40]. …”
Section: Hypoxic Preconditioningmentioning
confidence: 99%
“…This study also demonstrated the multilineage differentiation potential of DIAS cells by staining cultures for lipids, calcium deposits, and sulfated GAG and collagen type II after culture in adipogenic, osteogenic, and chondrogenic media, respectively [96]. In a separate study, chondrogenic differentiation of DIAS cells under hypoxia resulted in a 2.3-fold increase in collagen type II production per cell and a 1.2-fold increase in GAG content relative to normoxic culture [99].…”
Section: The Potential Of Dias Cells To Formmentioning
confidence: 53%
“…Another study using dermis MSCs confirmed that continuous hypoxic conditions (5% O 2 ) decreases the collagen type II to total collagen ratio; however, differentiation in hypoxic conditions following normoxic expansion increases production of collagen type II and GAGs. In that same study, expansion in hypoxia increased total matrix production [101]. Yet another study suggests that hypoxia alone has no effect on chondrogenesis or matrix synthesis, but that the effect is dependent on the hydrogel-scaffolding properties [96].…”
Section: Effect Of Hypoxia On Ac Differentiation Of Mscsmentioning
confidence: 91%